An epidemiological and genetic study of facial clefting in France. I. Epidemiology and frequency in relatives. Issue 1 (February 1982) - Bonaiti, C; Briard, M L; Feingold, J; Pavy, B; Psaume, J; Migne-Tufferaud, G; Kaplan, J
Abstract : The frequencies of cleft lip with or without cleft palate (CL(P)) and isolated cleft palate (CP) have been estimated in France to be 0.082% and 0.035%, respectively, after exclusion of malformation syndromes. A genetic and epidemiological study has been carried out on 468 patients with CL(P) and 163 with CP. The results are given in detail and some specific points are discussed: the apparently low incidence in France, the relationship between sex ratio and abortion rates, the maternal effects, and the possibility of an association between CL(P) and CP.